Investigando a Aprendizagem de Frações nas Séries Iniciais do Ensino Fundamental II - Beninca, Michele (2020)
The fraction is an elementary concept of great relevance in mathematics, but there are difficulties in learning for elementary school students. This research is a qualitative study with diagnostic evaluation that aims to investigate the difficulties in th